Innovative methodology for comprehensive utilization of refractory low-grade iron ores - Liang, Zhikai (2023)
The sustainable future of the steel industry crucially depends on the development of economical and environmentally responsible technologies to produce low-impurity iron powder from low-grade iron ores. Here, we developed an innovative process with low CO2 emission and energy consumption to comprehensively utilize high-silica low-iron ores from refractory waste. An excellent direct reduced iron powder containing 0.50% silica was obtained under optimum conditions with an iron recovery of 91.75%. Concomitantly, an excellent leach solution with high Si concentration and low impurities was obtained, which was appropriate to be processed into precipitated amorphous silica. The mechanism analysis revealed NaCl is involved in greatly reducing the theoretical formation temperature of metallic iron and significantly promoting the conversion of silicon minerals, thus facilitating the formation of the excellent DRI and leach solution. These findings highlight effectiveness of this novel approach in handling high-silica iron ores, eventually contributing to future sustainability of steel industry.